EFEKTIVITAS PROGRAM E-PARKING DALAM MEWUJUDKAN SMART CITY DI KOTA SEMARANG - Aprilia Rahmawati, Agnes; Maesaroh, Maesaroh; Widowati, Nina (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
The effectiveness of the e-parking program in Semarang City faces several challenges. This starts from the number of points as many as 436 points and 376 jukirs, making it difficult for jukirs to supervise 2 to 3 points at once which are located 1km on one road. In addition, the realization of PAD for 2022-2023 is not in accordance with the target set by the government. This study aims to analyze the effectiveness of the program and analyze various factors that drive and inhibit the effectiveness of the e-parking program in developing a smart city in Semarang City. This research method is qualitative descriptive with data collection techniques through interviews, documentation, and observation. The sampling used was snowball sampling and data validity through source triangulation. The data analysis techniques used are data reduction, data presentation, and conclusion drawn. The results of this study were analyzed using the Makmur theory while the driving and inhibiting factors were analyzed using Ripley's theory in Erwan and Dyah. Accuracy in carrying out orders, accuracy of targets, accuracy in determining time, accuracy in measurement have been effective, while accuracy in calculating costs, accuracy in making choices, accuracy in setting goals, accuracy in thinking have not been effective. The supporting factors include coverage, bias, and accountability, while the inhibiting factors are access, frequency, service accuracy, and program suitability. The recommendations of this study are to improve the expansion of access in making complaints, seek to understand the ease of electronic parking, seek to socialize e-parking to the public, seek to increase public awareness about easy, fast, and safe e-parking transactions, suggestions to minimize inhibiting factors related to access by providing socialization of complaints about e-parking, for frequency by seeking awareness of the convenience of e-parking in the community, for the accuracy of services with the socialization of e-parking in the community, for the suitability of programs related to the needs of the community that are easy, fast and safe with the socialization of e-parking in the community.